Comparison of Standard Absorbable Sutures with Self-Retaining Sutures in Retroperitoneoscopic Partial Nephrectomy: A Retrospective Study of 68 Patients - Xu, Weifeng; Li, Hanzhong; Zhang, Yushi; Zhang, Xuebin; Ji, Zhigang (Urology Journal, 2014)
Purpose: Although laparoscopic partial nephrectomy (LPN) has been increasingly adopted in the treatment of small localized renal tumor, technical changes remain nowadays. The current study aimed to evaluate the safety and efficacy of the novel QUILLTM Self-Retaining System (SRS) for renorrhaphy during LPN. Materials and Methods: Sixty-eight patients with kidney neoplasm that accepted LPN at the Peking Union Medical College Hospital from July 2010 to March 2013 were retrospectively analyzed. Thirty-five patients who received renal sutures with QUILLTM SRS constituted group 1. The control group (group 2) was composed of 33 patients who received standard absorbable Vicryl sutures by the same surgeon. Renorrhaphy was performed in both groups using two layers, with a closure of the deep vessels and collecting system, followed by a running closure of the renal capsule. The demographic and perioperative parameters (gender, laterality of the tumor, body mass index (BMI), tumor size, standardized nephrometry scoring system (R.E.N.A.L. Nephrometry Score), estimated blood loss and warm ischemic time (WIT)) were compared between the groups. Risk factors of WIT and blood loss were analyzed using logistic regression analysis. Results: Renorrhaphy was successfully completed in both groups. The baseline data of two groups did not differ significantly. Logistic regression analysis showed WIT decreased when the QUILLTM SRS was used (21.8 ± 3.5 min vs. 25.6 ± 4.0 min; ? = -4.109, P < .001). Suture methods were an independent predictor of WIT rather than blood loss (115.7 ± 57.9 mL vs. 137.9 ± 68.5 mL; P = .329). Conclusion: QUILLTM SRS can be effectively and safely used for renorrhaphy during LPN with the potential advantage of shortening WIT.